PENGEMBANGAN MEDIA PEMBELAJARAN TEMATIK- INTEGRATIF BERBASIS SOSIOKULTURAL BAGI SISWA KELAS IV SEKOLAH DASAR - Muhammad Abduh (Universitas Muhammadiyah Surakarta, 2015)
This study aims to produce the integrated thematic learning media based on sosiocultural on the themeof “indahnya kebersamaan” that is eligible effective for the fourth grade students of SDN Pujokusuman1 Yogyakarta. This study was a research and development (R D) based on Borg and Gall modelsthat was ellaborated by Sukmadinata into three groups: (1) preliminary studies, (2) development, and(3) testing and socializaton. The subjects of limited test are three expert validators and one personpracticioner validator. The subjects of main test are 29 fourth grade students of SDN Pujokusuman 1Yogyakarta. The research finding reveals that the learning instruments in terms of the learning mediaaccording to the experts are feasible to use, indicated by a mean score of Aiken’s V for each learninginstrument that is approaching 1, in other words the learning instruments have a very high validity andare feasible for use. Effectiveness testing that used before-after experimental design with the pre-testand post-test result shows a significant difference. The significance resulting from the calculation ofSPSS shows the number 0.0001 less than or equal with 0.05. Teacher activities before and when using the products increasedby 34.25%. Students activities before and when the products were applied increased by 38.89%.